"Regulation, I presume?" said the robot – Towards an iterative regulatory process for robot governance. Issue 6 (December 2018) - Fosch-Villaronga, Eduard; Heldeweg, Michiel
Abstract: This article envisions an iterative regulatory process for robot governance. In the article, we argue that what lacks in robot governance is actually a backstep mechanism that can coordinate and align robot and regulatory developers. In order to solve that problem, we present a theoretical model that represents a step forward in the coordination and alignment of robot and regulatory development. Our work builds on previous literature, and explores modes of alignment and iteration towards greater closeness in the nexus between research and development (R&D) and regulatory appraisal and channeling of robotics' development. To illustrate practical challenges and solutions, we explore different examples of (related) types of communication processes between robot developers and regulatory bodies. These examples help illuminate the lack of formalization of the policymaking process, and the loss of time and resources that the waste of knowledge generated for future robot governance instruments implies. We argue that initiatives that fail to formalize the communication process between different actors and that propose the mere creation of coordinating agencies risk being seriously ineffective. We propose an iterative regulatory process for robot governance, which combines the use of an ex ante robot impact assessment for legal/ethical appraisal, and evaluation settings as data generators, and an ex post legislative evaluation instrument that eases the revision, modification and update of the normative instrument. In all, the model breathes the concept of creating dynamic evidence-based policies that can serve as temporary benchmark for future and/or new uses or robot developments. Our contribution seeks to provide a thoughtful proposal that avoids the current mismatch between existing governmental approaches and what is needed for effective ethical/legal oversight, in the hope that this will inform the policy debate and set the scene for further research.